THE ROLE OF INTERNATIONAL REGIMES IN THE CONSTITUTION OF STATE BEHAVIOR AND IDENTITY: THE CASE OF CONTEMPORARY MEXICO - Anaya Muñoz, Alejandro (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2011)
This article explores the role played by international human rights regimes in the transnational and domestic politics of human rights of Mexico. Following international relations constructivists and liberal republican approaches, this article argues that international human rights regimes have played a key role in Mexico in the following ways: a) they have provided the normative standards, information about behavior, and necessary forums for processes of shaming and argumentation; b) regimes’ organs, bodies and mechanisms have been important actors in their own right in the aforementioned processes; c) regimes have been instrumental in the strategies of government elites seeking to secure their preferences in domestic politics. This article ends by offering a framework that might prove useful for understanding the role of international human rights regimes in other country-specific situations and by reflecting on the theoretical implications of its main argument.